Drug Discovery Concepts to Market - Bobbarala, Varaprasad (IntechOpen, 2018)
The book "Drug Discovery - Concepts to Market" is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the latest drug discovery trends that have been revolutionized with up-to-date technological developments. This book comprises single chapters authored by various researchers and edited by an expert active in the drug development research area. All chapters are independently complete but united under a common research study topic. This publication aims to provide a thorough overview of the latest research efforts in this field from international authors and open new possible research paths for further novel developments.